EFEKTIVITAS DAN EFISIENSI KERJA PEJABAT PEMBUAT AKTA TANAH DALAM DAERAH KERJA PROVINSI BERDASARKAN PERATURAN JABATAN PEJABAT PEMBUAT AKTA TANAH) - GORALISYAHPUTRA HASIBUAN HASIBUAN (PREMISE LAW JURNAL, 2017)
Abstract Land registration in Indonesia is regulated in Article 19, paragraph (1) of Law No. 5/1960 on Basic Regulation of the Agrarian Law which states that “in order to guarantee legal certainty, the government provides land registration in all over Indonesia according to legal provisions regulated by the Government Regulation.” The research used juridical normative method, using legislation approach. It also used prescriptive analytic method, using primary, secondary, and tertiary legal materials. The result of the research In this case, PPATs and public officials in the provincial working area are not able to do their job effectively and efficiently relating to the deeds they have made. It seems that the working area extension does not enable PPATs to do their performance effectively and efficiently in providing accuracy, certainty, and the truth of authentic deeds made before them since the Indonesian territory is varied and very large. Therefore, they are not able to do their job effectively and efficiently. Keywords: Effectiveness and Efficiency, PPAT and Work Area